2013
DOI: 10.1002/cne.23371
|View full text |Cite
|
Sign up to set email alerts
|

Choline acetyltransferase‐like immunoreactivity in a physiologically distinct subtype of olfactory nonspiking local interneurons in the cockroach (periplaneta americana)

Abstract: Behavioral and physiological studies have shown that local interneurons are pivotal for processing odor information in the insect antennal lobe. They mediate inhibitory and excitatory interactions between the glomerular pathways and ultimately shape the tuning profile of projection neurons. To identify putative cholinergic local interneurons in the antennal lobe of Periplaneta americana, an antibody raised against the biosynthetic enzyme choline acetyltransferase (ChAT) was applied to individual morphologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 89 publications
4
47
0
Order By: Relevance
“…To label putative GABAergic neurons in the brain of P. americana , we used a commercially available polyclonal antibody (Table , Cat# A2052, RRID: AB_477652, Sigma‐Aldrich) that was raised against a GABA‐bovine serum albumin (BSA) conjugate in rabbits. The resulting staining pattern was identical to that obtained in previous immunocytochemical studies in the protocerebrum (Yamazaki et al, ) and in the antennal lobe of P. americana (Distler, ; Fusca et al, ). According to the manufacturer's data sheet, the antibody showed positive binding with GABA and GABA‐KLH in a dot blot assay, and negative binding with BSA.…”
Section: Methodssupporting
confidence: 87%
“…To label putative GABAergic neurons in the brain of P. americana , we used a commercially available polyclonal antibody (Table , Cat# A2052, RRID: AB_477652, Sigma‐Aldrich) that was raised against a GABA‐bovine serum albumin (BSA) conjugate in rabbits. The resulting staining pattern was identical to that obtained in previous immunocytochemical studies in the protocerebrum (Yamazaki et al, ) and in the antennal lobe of P. americana (Distler, ; Fusca et al, ). According to the manufacturer's data sheet, the antibody showed positive binding with GABA and GABA‐KLH in a dot blot assay, and negative binding with BSA.…”
Section: Methodssupporting
confidence: 87%
“…Accordingly, we observed no hyperpolarization of the postsynaptic type I LN when the presynaptic uPN was hyperpolarized. In agreement with previous immunohistochemical and physiological studies, which suggested that uPNs are mostly cholinergic (Waldrop and Hildebrand, 1989;Homberg et al, 1995;Bicker, 1999;Homberg, 2002;Wilson et al, 2004;Fusca et al, 2013;Liu and Wilson, 2013), the excitatory synaptic transmission between uPNs and type I LNs could be reversibly blocked by the nicotinic acetylcholine receptor blocker mecamylamine (Fig. 2).…”
Section: Connections Between Uniglomerular Projection Neurons and Typsupporting
confidence: 91%
“…The study was conducted in the AL of the cockroach Periplaneta americana. In P. americana the physiology of the central olfactory neurons (Ernst and Boeckh, 1983;Lemon and Getz, 1997, 1998Strausfeld and Li, 1999;Husch et al, 2009a,b;Pippow et al, 2009) and the circuitry of the olfactory system have been analyzed in great detail down to the biochemical, structural, and ultrastructural level (Distler, 1989(Distler, , 1990Malun, 1991a,b;Malun et al, 1993;Distler and Boeckh, 1997a,b;Distler et al, 1998;Neupert et al, 2012;Fusca et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Within the brain cholinergic synaptic transmission is suggested to occur from axons of the olfactory receptor neurons onto local interneurons and projection neurons within the antennal lobes (in addition some of the local interneurons are cholinergic), from antennal lobe projection neurons onto mushroom body Kenyon cells and onto neurons of the lateral horn, between ocellar second-order neurons and their postsynaptic neurons. In addition, the insect central brain, optic lobes and the thoracic ganglia contain cholinergic neurons (e. g., Manduca sexta : [21], Schistocerca gregaria : [22], Periplaneta americana : [23], Drosophila melanogaster : [24], [25], [26], [27], Apis mellifera : [28]). Given this wide-spread central nervous distribution, it is not surprising that sublethal neonicotinoid doses compromise behavior and cognitive abilities also in honeybees including memory formation and retrieval [29], [30], social interactions, navigation and communication [11], [12] [31].…”
Section: Introductionmentioning
confidence: 99%